Potensi Implementasi Pendekatan Deep Learning dalam Pembelajaran Numerasi di Kelas 4 Sekolah Dasar - Nurahmadani, Anisa; Purnomo, Heru (Pendagogia: Jurnal Pendidikan Dasar, 2025)
Numeracy skills are an important component of mathematical literacy that need to be instilled from an early age so that students are able to face real-life problems logically and systematically. However, the reality on the ground shows that numeracy learning at the elementary school level still faces various obstacles, particularly in terms of learning approaches that do not fully encourage active involvement and in-depth student understanding. This study aims to describe the real conditions of numeracy learning implementation in fourth grade elementary schools based on observations and interviews, and explore the possibility of implementing a deep learning approach as an innovative strategy that is adaptive to the learning needs of 21st-century students. The study was conducted using a descriptive qualitative approach, through observations of numeracy learning and semi-structured interviews with class teachers. The results of the study indicate that conventional approaches are still dominant, with low student engagement and limited understanding of numeracy concepts, especially in fractions. Nevertheless, there are positive indications that the use of visual media and contextual activities can increase student enthusiasm and participation. These findings indicate that the deep learning approach has the potential to be integrated into numeracy learning, provided it is supported by increased teacher capacity and the provision of adequate digital learning infrastructure.